Pengaruh Model Pembelajaran Inkuiri Terbimbing Dengan Kontruktivisme Radikal Terhadap Berpikir Kritis Peserta Didik - Yusrizal Yusrizal; Ismul Huda; Suhrawardi Ilyas; Maghfirah Ulfa (Jurnal Penelitian Pendidikan IPA, 2022)
Lack of critical thinking of students in studying physics, this can be seen from their daily scores with an average of about 65.00 lower physics than other subjects. The purpose of this research problem is to determine the effect of guided inquiry learning model with radical constructivism on students' critical thinking skills. This type of research is using a quasi-experimental. The population in this study were all students of class VII MTsS Darul Ulum Banda Aceh, while the samples were taken by two classes by purposive sampling, namely class VII Experiment class (VII-1) which consisted of 30 students, while the control class (VII-3) consisted of 30 students consists of 30 students. The instrument used is a written test. The results showed that the average pre-test for the control class was 22.36, while the average for the experimental class was 32.16. These results show that the average pre-test for both the control class and the experimental class is still in the low category. And the average post-test for the control class is 47.60, for the experimental class is 64.25. This shows an increase in critical thinking in the control class through the guided inquiry learning model but it is still in the low category, namely 0.26, while the experimental class shows an increase in critical thinking through the guided inquiry learning model with radical constructivism of 0.50 in the medium category. This study proves that the inquiry learning model with radical constructivism can influence students' critical thinking